Experiential Learning With Children. Issue 4 (2015) - Schreiber, Joseph; Moerchen, Victoria A.; Rapport, Mary Jane; Martin, Kathy; Furze, Jennifer; Lundeen, Heather; Pelletier, Eric
<x xml:space="preserve">Abstract</x> Purpose: The Section on Pediatrics of the American Physical Therapy Association has developed a number of resources to support and improve the consistency of professional pediatric physical therapy education, including a set of core competencies that all graduates must attain. The purpose of this article is to advocate for the inclusion of experiential learning activities with children, including children with participation restrictions, as a necessary component to achieve the core competencies. Key Points: Experiential learning is a form of practice-based education that provides exposures and opportunities for students to explore the work, roles, and identities they will encounter as future professionals. Experiential learning is learning by doing, and occurs within a relevant setting. Six representative curricular exemplars are presented to provide readers with a variety of suggestions for development and integration of experiential learning. Summary: Recommendations for future research are provided and 4 key recommendations are provided.